PENGARUH PENERBITAN OBLIGASI SYARIAH TERHADAP PROFITABILITAS - Ikromi Ramadhani (Faculty of Economic and Business, 2013)
The aim of this research is to analyze the impact of Islamic bond issuance to company profitability. The company profitability is measured by return on asset (ROA) and return on equity (ROE). The method analysis that used in this study is simple linier regression with two variable dependent i.e. ROA and ROE, and one variable independent such as Islamic bonds issuance. The result showed that there is no influence on Islamic bond issuance to profitability in company that listed in Indonesian Capital Market. The reason of this result is because there is no direct impact on Islamic bonds issuance on company’s profitability. The Islamic bonds issuance had a direct impact on company’s funding for operational activitiesDOI: 10.15408/etk.v12i2.1914